Exploring the Integration of TPACK in Post-Pandemic Biology Education: A Study of Teachers in Magelang City - Muhammad Khoirul Antony; Sendy Putra Pradana; Ahmad Naharuddin Ramadhan; Susi Dewiyeti; Iful Amri (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
This research aims to explore deeper into the perspectives of biology teachers in the Magelang city regarding the crucial of TPACK in post-pandemic learning to support the professional development of teachers and create more relevant and high-quality learning. The method applied in this research is qualitative interviews. The respondents in this study consisted of 9 biology teachers in Magelang city. The TPACK framework is essential for effectively integrating technology, pedagogy, and content, though challenges remain in selecting appropriate tools and ensuring student engagement. The COVID-19 pandemic accelerated technology adoption, and teachers emphasized the need for continuous training and support to improve technology integration. Overall, with adequate resources and training, technology can greatly transform biology learning.